A comparative UHPLC-Q/TOF–MS-based eco-metabolomics approach reveals temperature adaptation of four Nepenthes species - Wong, Changi; Yee, Soon Ling; Lih, Julia Suan Wee; Aazani, Mujahid; Müller, Moritz (Springer Nature, 2020)
Nepenthes, as the largest family of carnivorous plants, is found with an extensive geographical distribution throughout the Malay Archipelago, specifically in Borneo, Philippines, and Sumatra. Highland species are able to tolerate cold stress and lowland species heat stress. Our current understanding on the adaptation or survival mechanisms acquired by the different Nepenthes species to their climatic conditions at the phytochemical level is, however, limited. In this study, we applied an eco-metabolomics approach to identify temperature stressed individual metabolic fingerprints of four Nepenthes species: the lowlanders N. ampullaria, N. rafflesiana and N. northiana, and the highlander N. minima. We hypothesized that distinct metabolite regulation patterns exist between the Nepenthes species due to their adaptation towards different geographical and altitudinal distribution. Our results revealed not only distinct temperature stress induced metabolite fingerprints for each Nepenthes species, but also shared metabolic response and adaptation strategies. The interspecific responses and adaptation of N. rafflesiana and N. northiana likely reflected their natural habitat niches. Moreover, our study also indicates the potential of lowlanders, especially N. ampullaria and N. rafflesiana, to produce metabolites needed to deal with increased temperatures, offering hope for the plant genus and future adaption in times of changing climate.